Higher education system in Malaysia: Exploring strategic trends and challenges in policy implementation for new Malaysia - Asmawi, Adelina; Jaladin, Rafidah Aga Mohd (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2018)
This research aimed at exploring and identifying the strategic trends and challenges that have emerged in higher education in Malaysia. A qualitative research approach was used to identify these trends and challenges using documentation and semi-structured interviews as the main data collection methods. The documents were books, newspaper articles, journals, and education blueprints. The interview samples were four education scholars who are leading figures from the Ministry of Education and public universities. To analyse the data, document examination and content analysis were carried out to identify emerging trends which involved several cycles of coding. These trends were found to be parallel to the changes in the Malaysian higher education system in an attempt to upgrade its quality and sustainability, and to keep abreast with the current waves of globalisation, internationalisation and societal change. They are part of processes adopted by the Malaysian Education Ministry in ensuring that the country is not left behind in providing quality tertiary education for the nation. The ramifications of these trends and their associated challenges were discussed within the Malaysia Higher Education Blueprint framework. The implications for improving the quality of higher education are also included.